2015
DOI: 10.1021/bi501483q
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Attack of Escherichia coli by the Antimicrobial Peptide Human Defensin 5

Abstract: Human α-defensin 5 (HD5) is a 32-residue cysteine-rich host-defense peptide that exhibits broad-spectrum antimicrobial activity and contributes to innate immunity in the human gut and other organ systems. Despite many years of investigation, its antimicrobial mechanism of action remains unclear. In this work, we report that HD5ox, the oxidized form of this peptide that exhibits three regiospecific disulfide bonds, causes distinct morphological changes to Escherichia coli and other Gram-negative microbes. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 71 publications
4
89
0
1
Order By: Relevance
“…Peptide entering the cytosol will then induce multiple cellular damages, as observed with blebbing and clumping of cells. Extensive elongation of cells was also noted, indicating disruption to cell division events (124). Such treatment outcomes were observed in P. aeruginosa, K. pneumoniae, and Acinetobacter baumannii, suggesting that HD5 produced a common inhibitory activity against Gram-negative bacteria.…”
Section: Cell Division Inhibitorsmentioning
confidence: 81%
“…Peptide entering the cytosol will then induce multiple cellular damages, as observed with blebbing and clumping of cells. Extensive elongation of cells was also noted, indicating disruption to cell division events (124). Such treatment outcomes were observed in P. aeruginosa, K. pneumoniae, and Acinetobacter baumannii, suggesting that HD5 produced a common inhibitory activity against Gram-negative bacteria.…”
Section: Cell Division Inhibitorsmentioning
confidence: 81%
“…6), blebs almost always occur as multiple protrusions per cell [171,[182][183][184]. Blebs are also typically smaller than bulges (diameters of just 10-100nm) [26,184], though enlargement and peptidoglycan rupture during some treatments allows them to develop into bulges [179]. Bleb formation occurs following treatment with membrane-active agents [24,41,181,184] and inhibitors of RNA [143] and protein synthesis [83,179,181].…”
Section: Blebbingmentioning
confidence: 99%
“…A forerunner of the molecular biology approach was the examination of bacteria treated with test agent for changes to their morphology and ultrastructure [24]. This strategy remains extremely popular among researchers investigating antibacterial mechanism of action, both as an early exploratory step [26][27][28][29][30] and for confirmation of a suspected mechanism [31][32][33]. Requiring only access to an electron microscopy suite, it is an approach that is open to researchers in even relatively low resource settings.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have, however, shown that a concentration between 3.1μM [170] to 20μM [124] (depending on the experimental set up) is sufficient to guarantee zero survival of E.coli. However, in these studies the experimental set up differed from the one that was used in our research since the bacteria were directly exposed to human α-defensin 5 and the cell bacteria interaction process was excluded.…”
Section: Paper III and Ivmentioning
confidence: 94%
“…Earlier they were thought to do so by destroying the bacterial membrane [119], however, this does not stand to be true. Recent studies have indicated that human α-defensin 5 and human α-defensin 6 do not permeabilize bacterial membranes, instead they eradicate bacteria by localizing to the cytoplasm and possibly interacting with DNA [124].…”
Section: Defensinsmentioning
confidence: 99%